A study of crime potentials in Taman Melati terrace housing in Kuala Lumpur : issues and challenges - Elsawahli, Hanan Mohamed Hassan (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2010)
Malaysia has recently been experiencing rapid urbanization. This rapid urbanization is associated with increasing crime problems in towns and cities. Crimes in housing areas has become a fact of life with street crimes increasing, crimes against persons and properties generating considerable fear within the community making safety an issue demanding a critical attention at both local and national level. Recently Malaysia has adopted the “Safe City Program” initiated by the Ministry of Housing with the cooperation of the Federal Department of Town and Country Planning in 2005, which is focused towards achieving four objectives, the most important of which is creating a city free from violence and crime. In order to achieve a the global concern of creating sustainable communities and to assist the implementation of Malaysia's safe city program which highlights the importance of quality of life improvements it is important to address crime and disorder through studies and research. Studies have identified that changes to the built environment and modifications to the space design can effectively affect both residents and offenders perceptions of criminality. Various place-based crime prevention techniques are employed to create a place that is easy to defend. The main aim of the research is to examine the effectiveness of these techniques in providing a safe environment. Two housing locations (AMR and AOS) in Taman-Melati terrace houses were chosen for the study. To achieve the objectives and answer the research questions a triangulation approach was used in which data is obtained from both quantitative methods (questionnaire and observation) and qualitative methods (interviews). The data was analysed using SPSS. Reliability test was carried to examine the reliability of the factors in measuring the safety level. Cross tabulation, t-test, chi-square and correlation were used to identify the impact of the physical factors on the safety level. The findings showed that the crime risk was higher in the AOS terrace houses than in AMR terrace houses. All the factors showed correlation with the safety level except for omni-presence. It was also found that most of the break-ins were through the front door and that the most frequent crime is street snatching. Recommendations included enhancement of the natural surveillance, installing higher perimeter fencing, provision for adequate lighting for pedestrian walk, Provision of adequate pedestrian walk and educational and awareness programs for the residents. Future studies are recommended to cover neighbourhood safety based on an analysis of safe streets, effect of ethnicity and religiosity on safety level and a comparative study between walk-up apartments and condominiums to help policy makers select which housing type should be further developed in order to achieve the safe city program